2014
DOI: 10.1017/s0007114514000610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary microencapsulated sodium butyrate on growth, intestinal mucosal morphology, immune response and adhesive bacteria in juvenile common carp (Cyprinus carpio) pre-fed with or without oxidised oil

Abstract: The aim of the present study was to investigate the effects of different dietary sustained-release microencapsulated sodium butyrate (MSB) products (0 (non-supplement), 1·5 and 3·0 h) for a control or oxidised soyabean oil (SBO) diet on fish production, intestinal mucosal condition, immunity and intestinal bacteria in juvenile common carp (Cyprinus carpio). Dietary MSB increased weight gain and reduced the feed conversion ratio within the control and oxidised SBO groups. Gut mucosa was damaged in the oxidised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
148
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(171 citation statements)
references
References 45 publications
16
148
0
Order By: Relevance
“…This receptor has anti-inflammatory properties acting as the metabolite sensor of butyrate, the end product of the microbial fermentation of dietary fiber (Singh et al, 2014). This short-chain fatty acid has been considered a promising feed additive in aquaculture, improving the immunological status and intestinal condition in carp ( Cyprinus carpio ) (Liu et al, 2014). Recent data also support the promising effects of butyrate supplementation in European sea bass, and Rimoldi and co-workers have found reported improved growth and increased gene expression of the oligopeptide transporter 1 ( PEPT1 ) in the hindgut of fish fed low-fish meal diets (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…This receptor has anti-inflammatory properties acting as the metabolite sensor of butyrate, the end product of the microbial fermentation of dietary fiber (Singh et al, 2014). This short-chain fatty acid has been considered a promising feed additive in aquaculture, improving the immunological status and intestinal condition in carp ( Cyprinus carpio ) (Liu et al, 2014). Recent data also support the promising effects of butyrate supplementation in European sea bass, and Rimoldi and co-workers have found reported improved growth and increased gene expression of the oligopeptide transporter 1 ( PEPT1 ) in the hindgut of fish fed low-fish meal diets (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al . () observed slight alterations in the adherent bacterial communities within the gut segments of common carp fed 0.3 g kg −1 Na‐butyrate diets. Zhou et al .…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 93%
“…In common carp, it had similarly been reported that the intestinal mucosal morphology was not significantly altered when fish were fed diets supplemented with Na‐butyrate although some differences were observed in microvillus height (Liu et al . ). Apart from the slight improvement in weight gain, FCR and immune responses, it was reported that dietary Na‐butyrate seemed to be able to prevent or repair the intestinal mucosal damage and increase the microvillus density in carp prefed with oxidized soya bean oil.…”
Section: Mode Of Action and Effects Of Dietary Organic Acidsmentioning
confidence: 97%
“…In fish, dietary butyrate is able to improve growth and feed utilization in carp [22, 23], although no consistent effects have been reported in rainbow trout [24]. By contrast, in gilthead sea bream, dietary butyrate has been shown to provide energy for the epithelial intestine with a slight improvement of growth rates [25].…”
Section: Introductionmentioning
confidence: 99%